Consumption-Based Water Footprint Analysis of Food and Non-Food Sectors for Sustainable Management of the Jambo Aye Watershed - Nabila Sam Dwitara; Purwana Satriyo; Syahrul (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Water is a vital resource that supports the sustainability of life and the economic activities of communities. This study analyzes the water footprint (WF) of food and non-food consumption as a basis for water resource management in the Jambo Aye Watershed, Aceh Province, Indonesia. A quantitative descriptive approach was applied using secondary data on household food and non-food consumption from the National Socio-Economic Survey (SUSENAS) of Statistics Indonesia (BPS) and population data for 2023 and 2024. The WF was calculated by multiplying the per capita consumption of each commodity by its virtual water coefficient, adopting the standardized global coefficients of the Water Footprint Network (Mekonnen & Hoekstra), and aggregating the results at the watershed scale; the analysis employed total (aggregate) virtual water values without disaggregating the green, blue, and grey components. The results show that the WF of food consumption reached 688.90 million m³ in 2023 and increased by 8.27% to 745.84 million m³ in 2024, accounting for more than 99% of the total WF, with rice as the main contributor. The WF of non-food consumption was considerably smaller, rising by 9.11% from 3.00 million m³ in 2023 to 3.28 million m³ in 2024, driven mainly by housing and household facilities. These findings indicate that water resource management in the Jambo Aye Watershed should prioritize improving water-use efficiency in the food sector, particularly rice-based agriculture, to support the long-term sustainability of water resources.